Jurisdicción real y asilo eclesiástico en Sempere y Guarinos: el “caso Anze” - Herrera Guillén, Rafael (Cuadernos de Historia del Derecho, 2007)
Alegaciones por la jurisdicción real, en el recurso de fuerza sobre la inmunidad de Francisco Anze y Torres, was written by Sempere y Guarinos in the days when he was already a public prosecutor at the Chancillería of Granada. It aims to demonstrate the temporary homogeneity of the secular and ecclesiastical authority. Some years later, in Recursos de fuerza, another of his works, he insists again on this same thesis. With the analysis of these two works we try to surpass the thesis that affirms that Sempere’s public prosecutor profession was an obstacle for the unfolding of his historical sense.